Insights into Agricultural-Waste-Based Nano-Activated Carbon Fabrication and Modifications for Wastewater Treatment Application - Muhammad, Syaifullah; Abdul Khalil, H. P. S.; Abd Hamid, Shazlina; Albadn, Yonss M.; Suriani, A. B.; Kamaruzzaman, Suraiya; Mohamed, Azmi; Allaq, Abdulmutalib A.; Yahya, Esam Bashir (Agriculture (Basel), 2022)
The past few years have witnessed extensive global industrial development that has led to massive pollution to most available water resources. There is no alternative to sustainable development, and the utilization of agricultural waste for wastewater treatment has been always a novel milestone in sustainable development goals. Agricultural-waste-based nano-activated carbon exhibits high porosity, great surface area, and unique surface functional groups that promote it to becoming a future and sustainable solution for wastewater treatment applications. Several modification approaches have been made to further enhance the adsorption capacity and reusability of such adsorbents. In this review, we presented the potential of agricultural-waste-based nano-activated carbon as a sustainable solution for wastewater treatment. We highlighted the fabrication process and properties of different nano-activated carbons in addition to different modification approaches to enhance its adsorption capacity. Finally, we critically discussed the recent advances in nano-activated carbon applications in water treatment including its role in drinking water filtration, organic dye removal, oil spill applications, heavy metals removal and the elimination of toxic compounds from wastewater.